A modular multifidelity approach for multiphysics oleo-pneumatic shock absorber simulations - Sheikh Al-Shabab, Ahmed A.; Silva, Paulo A. S. F.; Grenko, Bojan; Tsoutsanis, Panagiotis; Skote, Martin (Springer Nature, 2024)
A numerical framework is developed and tested to simulate the internal dynamics of oleo-pneumatic shock absorbers. A modular approach is devised to address the multiphysics nature of the problem, starting with three dimensional scale resolving turbulence simulations and two dimensional axisymmetric multiphase URANS simulations. These simulations capture the main dominant aspects of energy dissipation through turbulence, and the multiphase mixing which can affect the working fluid properties. Internal flow simulations are run on a representative shock absorber geometry based on dimensions provided in the validation study together with sizing guidelines from the literature. A lower fidelity two-equation dynamic system solver is used to scan the design space and test the sensitivity towards various design parameters, in addition to identifying parameter combinations that would be of interest to investigate using higher fidelity methods.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering